Teachers' Perception on School Health Services - Poudel, Arjun Prasad (Journal of Health Promotion, 2018)
Teaching health and physical education by qualified teachers can support the promotion of health among school children. In Nepal, school health programme has not been run effectively as health and any subject teachers teach physical education subject. On the other hand, government policy makers and school management does not seem serious about this issue. In this context, the study intends to explore perceptions of teachers on students' health promotion through school health services. This study was based on qualitative research design specifically phenomenological approach. Qualitative data were collected from twelve purposefully selected teachers of six different community schools of Kathmandu using in- depth interview technique. The collected data were analyzed by applying thematic approach. The study collected perception of Health and Physical Education (HPE) teachers regarding school health services, health promotive activities, water, sanitation and hygiene that play crucial role to promote healthy behaviour of students. In their perception, school health services should be provided to promote students' health, control the epidemics and communicable diseases and to create healthy school environment. In their perception, child friendly school creates an open-learning environment and keeps students mentally sound, creative and well-motivated in learning. Based on the findings of the study, it can be concluded that teachers' perception on school health programme is fairly satisfactory. However, their health activities are limited within the classroom practices and theoretical notions included in the textbook.Journal of Health Promotion Vol.6 2008, p.5-10